Seeing pain and pleasure on self and others: behavioral and psychophysiological reactivity in immersive virtual reality - Fusaro, M. (J Neurophysiol, 2016)
Studies have explored behavioral and neural responses to the observation of pain in others. However, much less is known about how taking a physical perspective influences reactivity to the observation of others' pain and pleasure. To explore this issue we devised a novel paradigm in which 24 healthy participants immersed in a virtual reality scenario observed a virtual: needle penetrating (pain), caress (pleasure), or ball touching (neutral) the hand of an avatar seen from a first (1PP)- or a third (3PP)-person perspective. Subjective ratings and physiological responses [skin conductance responses (SCR) and heart rate (HR)] were collected in each trial. All participants reported strong feelings of ownership of the virtual hand only in 1PP. Subjective measures also showed that pain and pleasure were experienced as more salient than neutral. SCR analysis demonstrated higher reactivity in 1PP than in 3PP. Importantly, vicarious pain induced stronger responses with respect to the other conditions in both perspectives. HR analysis revealed equally lower activity during pain and pleasure with respect to neutral. SCR may reflect egocentric perspective, and HR may merely index general arousal. The results suggest that behavioral and physiological indexes of reactivity to seeing others' pain and pleasure were qualitatively similar in 1PP and 3PP. Our paradigm indicates that virtual reality can be used to study vicarious sensation of pain and pleasure without actually delivering any stimulus to participants' real body and to explore behavioral and physiological reactivity when they observe pain and pleasure from ego- and allocentric perspectives.